Clinical decision-making of bachelor and clinical internship (professional) nursing students in Indonesia - Annissa Novalia; Shanti Farida Rachmi; Krisna Yetti (SAGE Publishing, 2021)
Background: Clinical decision-making is an essential element of every professional nursing career. A nurse's aptitude for clinical decision-making influences the quality of the healthcare they provide. This research aims to describe the clinical decision-making among nursing students at Universitas Indonesia. Design and Methods: This research employed a cross-sectional design by sampling 216 students across several types and level of students programs in the University. The samples were selected using a stratified random sampling technique and met the inclusion criteria. The instrument of this research was the 2014 Nursing Decision Making Instrument (NDMI-R2014).  The survey instrument was translated from English into Indonesian, and its validity and reliability were tested (α Cronbach value = 0.816). Results: The results of the univariate analysis revealed that students' clinical decision-making abilities vary; 59.2% in the analysis category, 40.3% in the quasi-rational category, and 0.5% in the intuitive category. Conclusion: This research concludes that the clinical decision-making ability of bachelor and professional nursing students program is in the analysis category which indicate that students' clinical decision-making abilities involve their explicit-theoretical knowledge and are supported by evidence-based practices. Therefore, their clinical decision-making can be logically defended, though it requires a longer duration of time to strengthen those abilities.  The students' clinical decision-making must continuously be improved to enable them to create precise decisions based on various situations and clinical conditions.